Analisis konservasi kawasan banjir di Jakarta Pusat (studi kasus Kecamatan Gambir) - Suryanti, Titien; Seanders, Olivia (Jurnal Arsitektur Lansekap; Vol.6, No.2, Oktober 2020, 2020)
Conservation Analysis of Flood Area In Jakarta Pusat (Case Study: Gambir Sub-District). The city's development as one of the primary government centers has experienced various changes in the land's physical environment, which are increasingly dense by various infrastructures to impact the quality of people's lives and the environment. This study aims to achieve a healthy ecological system by conserving flood-prone areas as human needs for a healthy environment. This research took place in the Gambir Subdistrict, Central Jakarta Municipality, Special Region of Jakarta Province, with an area of 7.59 km2. The method used in this paper is a descriptive analysis using secondary data. Based on the analysis of land use maps, green open space maps, land subsidence maps and topography, yielded three Conservation Area categories in Gambir District, namely (a) High Category, covering urban villages (Kelurahan) of Kebon Kelapa and Gambir (b) Medium category,  covering urban villages of Duri Pulo and Cideng (c) Low Category, covering urban villages of North Petojo and South Petojo areas.